Association of Polar Early Career Scientists Promotes Professional Skills. Issue 24 (17th June 2014) - Pope, Allen; Fugmann, Gerlis; Kruse, Frigga
<x xml:space="preserve">Abstract</x> As a partner organization of AGU, the Association of Polar Early Career Scientists (APECS; http://www.apecs.is) fully supports the views expressed in Wendy Gordon's Forum article "Developing Scientists' 'Soft' Skills" (Eos, 95(6), 55, doi:10.1002/2014EO060003). Her recognition that beyond research skills, people skills and professional training are crucial to the success of any early‐career scientist is encouraging.